A Contextual Da'wah Model in Indonesian Islam: Examining the Thought of AGH Sanusi Baco - Suhardi (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Contemporary da‘wah studies have predominantly focused on digital preaching, Islamic popular culture, and transnational religious movements, while paying limited attention to contextual da‘wah models rooted in the intellectual traditions of local Indonesian ulama. As a result, the interaction between maslahat-oriented Islamic reasoning, ethical communication, and charismatic religious authority in shaping adaptive da‘wah practices remains insufficiently explored. This study aims to analyze the da‘wah thought of AGH. Sanusi Baco, examine audience perceptions of his preaching practices, and formulate a contextual maslahat-oriented da‘wah framework. This research employs a qualitative approach using observation, in-depth interviews, and documentation as primary data collection techniques. The data were analyzed through an interactive model consisting of data reduction, data display, and conclusion drawing. Data credibility was ensured through source triangulation, methodological triangulation, and member checking with informants. The findings demonstrate that AGH. Sanusi Baco’s da‘wah is constructed through three interconnected dimensions: first, maslahat-oriented fiqh reasoning grounded in fiqh al-awlawiyyāt; second, ethical communication characterized by simplicity, gentleness, and a non-confrontational approach; and third, moral authority established through exemplary conduct and ethical consistency. This study proposes a contextual maslahat-oriented da‘wah framework integrating rational religious consideration, ethical message delivery, and personal integrity as the basis of effective preaching. The novelty of this study lies in its integrative framework connecting Islamic legal reasoning, interpersonal da‘wah communication, and charismatic authority within the tradition of local Indonesian ulama. Theoretically, the study enriches contemporary da‘wah scholarship, while practically offering an analytical model for adaptive and socially inclusive da‘wah practices in plural Muslim societies.